Environmental, Social, and Governance (ESG) Scores and Financial Performance of Publicly Listed Companies in Turkey - Özer, Gökhan; Aktas, Nagihan; Cam, Ilhan (Eskisehir Osmangazi Univ, Fac Education, 2023)
In this paper, the question of whether the efforts of businesses on environmental, social and corporate governance (ESG) investments are also reflected in their financial performance is tried to be answered. In this context, the effects of ESG scores of non-financial firms between 2009-2019 on market-based and accounting-based performance indicators were examined. According to the findings, ESG scores positively affect the performance indicators of companies. According to the results of the additional analyzes using the sub-components of the ESG, it was found that while all three components of the environmental dimension affect performance positively, some sub-components related to the social and corporate governance dimensions are not statistically related to performance.
Keywords: Environmental; social; and governance (ESG); Performance; Tobin's Q; Return of assets; Return of equity